Protracted Development on Native Tone Interpretation: Evidence From Mandarin-Learning Infants’ Novel Word Learning - Zheng, Xiaobei; Ji, Yinglin; Meng, Xiangzhi (Frontiers in Psychology, 2019)
Studies have shown that infants from cultures with tone languages develop categorical perception of their native lexical tone before their first birthday, but few studies have explored whether, and when, they interpret the phonemic function of lexical tone in word learning. Two habituation-switch experiments were conducted to explore whether Mandarin-learning infants could exploit tonal cues during their word learning, and detect a change when the association of two word-object pairs was switched. In Experiment 1, two words were solely differentiated by their lexical tones (/fāi/ vs. /făi/), and Mandarin-learning infants failed to detect the switch of tones at 14 months, but succeeded at 18 months. In Experiment 2, two words were markedly distinct (/fāi/ vs. /bǒu/), and infants could detect the change of words as early as 14 months. The results indicate that infants may not refer to the lexical function of tone during their novel word learning until 18 months, even though infants from birth are able to distinguish the Tone 1 vs. Tone 3 contrast. Given that lexical tone is expressed by variations of the pitch contours, which are also related to intonation, infants’ increasing knowledge of both tone and intonation may contribute to their misinterpretation of pitch contours in word learning at 14 months and, further, to their development of a sophisticated use of the phonemic function of lexical tone at 18 months of age.